(untitled) - Scruggs, Lyle (Cambridge, UK, 2003)
Representing the first comprehensive study of its kind, this book evaluates the comparative performance of national environmental policies since the beginning of the modern environmental era. Unlike other comparative studies, it looks directly at the purpose of environmental policy: pollution reduction.
Keywords: Environmental policy,Environmental economics,Sustainable development,Chính sách môi trường,Kinh tế môi trường; Phát triển bền vững